Project-Based Learning Assessment Guidebook Project-Based Assessment with Design Approach Thinking - Putri, Putu Lanny Kristina; Widiana, I Wayan; Suarjana, I Made (Universitas Pendidikan Ganesha, 2024)
This developmental research is motivated by the lack of critical thinking skills in mathematics among fifth-grade elementary school students. This issue arises from the absence of guidelines to assist teachers in the teaching and assessment process, resulting in a monotonous learning experience. The research aims to produce a valid, practical, and effective guidebook to enhance critical thinking skills in mathematics. The method employed is developmental research using the 4D (Four-D) model, involving 4 assessment experts, 3 practitioners, and 20 fifth-grade elementary school students as research subjects. Data are collected through both test and non-test methods, utilizing questionnaires and tests as instruments. Data analysis involves descriptive qualitative, quantitative, and inferential statistical analyses. The research findings indicate that the assessment guidebook receives excellent validation from experts and highly positive feedback from teachers regarding its practicality. Furthermore, the guidebook significantly improves the critical thinking skills of fifth-grade students in mathematics. Thus, the project-based assessment guidebook with a design thinking approach is deemed suitable, practical, and effective. The implication of this research is that the guidebook can serve as a reference for teachers in conducting assessments.